Regional imbalances of market efficiency in China’s pilot emission trading schemes (ETS): A multifractal perspective - Chai, Shanglei; Yang, Xiaoli; Zhang, Zhen; Abedin, Mohammad Zoynul; Lucey, Brian (Research in international business and finance, 2022)
China's emission trading schemes (ETS) have caused great concern worldwide. Exploring the regional imbalance of market efficiency in China's pilot ETS is a crucial task. We use empirical mode decomposition (EMD)-based multifractal detrended fluctuation analysis (MFDFA) to analyze market efficiency of China's pilot ETS. The contributions are as follows. First, the multifractal features of China’s pilot ETS have been discovered. Second, China’s pilot ETS are subject to a high risk of price fluctuations and market risk can be arranged from highest to lowest as Shanghai, Tianjin, Shenzhen, Guangdong, Hubei, Beijing, Chongqing, and Fujian. Third, market efficiency can be arranged from highest to lowest as Chongqing, Fujian, Hubei, Guangdong, Shanghai, Shenzhen, Beijing, and Tianjin. Fourth, the sources of multifractal features of China’s pilot ETS were investigated. This paper provides new ideas for studying market efficiency of China's ETS and policy implications for risk prevention. [Display omitted] •Using EMD-MFDFA to study China’s carbon market.•Results support fractal markets hypothesis (FMH).•Market risk of China’s pilot ETS can be arranged.•The regional imbalance of market efficiency does exist.•The sources of multifractal features are investigated.